Separation of Radiocopper 64/67Cu from the Matrix of Neutron-Irradiated Natural Zinc Applicable for 64Cu Production - S. Soenarjo; Sriyono Sriyono; W.Y. Rahman; E. Sarmini; Hambali Hambali; Triyanto Triyanto (Atom Indonesia, 2012)
Radioisotope 64Cu is a promising radiometallic-isotope for molecular-targeted-radiopharmaceuticals. Having a half-life of 12.70 hours and emitting β+-radiation (Eβ+ = 0.6531 MeV) as well as β-ray (Eβ- = 0.5787 MeV), it is widely used in the form of biomedical-substrate-radiopharmaceutical for positron emission tomography (PET) diagnosis and simultaneously for targeted radiotherapy of cancer. The potential needs on the availability of 64Cu-labeled pharmaceuticals for domestic nuclear medicine hospitals lead to a necessity for the local production of carrier-free 64Cu using BATAN’s G.A. Siwabessy reactor because of the technical and economical constraints in the production using BATAN’s cyclotron. The presented work is accordingly to study whether the radioisotope 64Cu can be produced and separated from the matrix of post-neutron-irradiated-natural zinc. This study is expected can be further improved and implemented in production technology of carrier-free 64Cu based on 64Zn (n,p) 64Cu nuclear reaction exploiting the fast neutron fraction among the major thermal fraction due to unavailability of fast-neutron-irradiation facility in the BATAN’s G.A. Siwabessy reactor. The solution of post-neutron-irradiated-natural zinc in 1M acetic acid was loaded into Chelex-100 cation exchanger resin column to pass out the Zn/Zn* fraction whereas the Cu* fraction which remained in the column was then eluted out from the column by using 1.5 M HCl and loaded into the second column containing Dowex-1X8 anion exchanger resin. The second column was then eluted with 0.5 M HCl. The collected eluate was expected to be zinc-free Cu* fraction. It was observed from the half-life and the γ-spectrometric analysis that radioactive copper-64Cu containing 67Cu was produced by neutron activation on the natural Zn-foil target and can be separated from the target matrix by the presented two-steps-column-chromatographic separation technique. The radioactivity measurement showed that wrapping the Zn target with cadmium foil increased the activity of radioactive copper and, thus, the Cu*/Zn*-ratio.Received: 28 June 2011; Revised: 21 February 2012; Accepted: 24 February 2012